2019 IEEE/ACM Third Workshop on Deep Learning on Supercomputers (DLS) 2019
DOI: 10.1109/dls49591.2019.00008
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Accelerated Light Source Experiments

Abstract: Experimental protocols at synchrotron light sources typically process and validate data only after an experiment has completed, which can lead to undetected errors and cannot enable online steering. Real-time data analysis can enable both detection of, and recovery from, errors, and optimization of data acquisition. However, modern scientific instruments, such as detectors at synchrotron light sources, can generate data at GBs/sec rates. Data processing methods such as the widely used computational tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 52 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…SSIM is improved significantly by TomoGAN and is improved consistently across all the slices, suggesting that the method is reliable. The evaluation of this low-dose scenario can also be used for streaming tomography where the views are very limited at the beginning of experimentation (e.g., Liu et al 2019 [55] 128 projections 64 projections…”
Section: Fewer Projectionsmentioning
confidence: 99%
“…SSIM is improved significantly by TomoGAN and is improved consistently across all the slices, suggesting that the method is reliable. The evaluation of this low-dose scenario can also be used for streaming tomography where the views are very limited at the beginning of experimentation (e.g., Liu et al 2019 [55] 128 projections 64 projections…”
Section: Fewer Projectionsmentioning
confidence: 99%
“…To explore whether a particular deep learning model can provide sufficient accuracy on edge devices, TomoGAN (94,95), which is an algorithm for enhancing the quality of X-ray images, was adapted to run on the Google Edge TPU and NVIDIA Jetson TX2 (96). The benchmarking results indicated that edge accelerators can provide sufficient accuracy with a novel shallow CNN called the fine-tune network.…”
Section: System Under Testmentioning
confidence: 99%
“…Many machine learning (ML) techniques have been successfully used and integrated to light source and electron microscopy data analysis workflows to enhance and improve the quality of images and reconstructions [9,36,56], including image denoising [62,39], artifact reduction [65] and feature extraction [51]. These techniques can also be used for accelerating the performance of workflows and data acquisition [38]. We plan to incorporate some of these advanced ML techniques in our workflow in the future.…”
Section: Related Workmentioning
confidence: 99%